2009
DOI: 10.1016/j.bone.2009.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed genes between osteoblasts and osteocytes

Abstract: Osteocytes represent the most abundant cellular component of mammalian bones with important functions in bone mass maintenance and remodeling. To elucidate the differential gene expression between osteoblasts and osteocytes we completed a comprehensive analysis of their gene profiles. Selective identification of these two mature populations was achieved by utilization of visual markers of bone lineage cells. We have utilized dual GFP reporter mice in which osteocytes are expressing GFP (topaz) directed by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
197
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(212 citation statements)
references
References 46 publications
13
197
2
Order By: Relevance
“…Our previous work identifying CTR expression in osteocytes made use of calvarial bone specimens in young mice (Gooi et al 2010), and the same is true of the work of Paic et al (2009) that described Calcr in isolated osteocytes. Our current work suggests that CTR expression by osteocytes is not constant, but is reduced as rodents age, most dramatically in the long bones.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Our previous work identifying CTR expression in osteocytes made use of calvarial bone specimens in young mice (Gooi et al 2010), and the same is true of the work of Paic et al (2009) that described Calcr in isolated osteocytes. Our current work suggests that CTR expression by osteocytes is not constant, but is reduced as rodents age, most dramatically in the long bones.…”
Section: Discussionmentioning
confidence: 90%
“…In addition to any coupling-mediated actions, we found that sCT treatment also increased the expression of sclerostin (Gooi et al 2010), an inhibitor of bone formation that is secreted by osteocytes. This stimulation of sclerostin by sCT is likely to be mediated by CT receptors (CTRs) that we, and others, identified in bone matrixembedded osteocytes (Paic et al 2009, Gooi et al 2010. PTH anabolic action suppresses sclerostin production (Bellido et al 2005, Leupin et al 2007 and PTH anabolic action is limited in mice that overexpress sclerostin (Kramer et al 2010).…”
Section: Introductionmentioning
confidence: 80%
“…In contrast, these cells had low levels of expression of genes characteristic of immature osteocytes and late osteoblasts, such as keratocan (Fig. 2B) (42,43). After 1 week in culture at 37°C, Ocy454 cells expressed levels of DMP1 (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, it was recently demonstrated that bone homeostasis and adaptation to regular or diminished skeletal loading are strongly disturbed in mice selectively depleted of osteocytes (61). Therefore, while osteocytes are cellular descendants of former bone matrix-producing osteoblasts, osteocytes have a unique cellular identity that is reflected by their specific location inside the bone matrix, their specialized cellular morphology adapted to being trapped in the mineralized bone compartment, and finally a specific molecular signature that clearly distinguishes osteoblasts and osteocytes from each other (52).…”
mentioning
confidence: 99%